Pengembangan Media E-Learning Berbasis Weblog dengan Pendekatan Contextual Teaching and Learning (CTL) pada Materi Laju Reaksi - Rumahorbo, Shinta; Nurfajriani, Nurfajriani (CV. Publikasi Indonesia, 2022)
This study aims to find out the analysis of media needs, look for e-learning media based on weblogs with a CTL approach on reaction rates developed based on BSNP and knowing students' responses to webblog-based e-learning media with a CTL approach on the reaction rate material. Analysis of media needs was carried out by interviewing the chemistry class teacher of SMAN 1 Sibolga. This study uses the method (R&D) with the ADDIE development model covering the stages (analysis, design, development, implementation and evaluation). The developed media product was validated by 3 expert validators consisting of 2 chemistry lecturers and 1 chemistry teacher. The average result of the validation of the weblog-based e-learning media with the CTL approach that has been developed by chemistry lecturers and teachers is 3.70 in the very feasible category and material validation is 3.71 in the very feasible category and does not need to be revised. The assessment of the percentage of student responses to the web-based e-learning media developed was 74.5% with high response criteria